The Application of Reader-response Theory in Enhancing Student Teachers’ Affective and Linguistic Growth: A Classroom Action Research in EFL Teacher Education in Indonesia - ISKHAK (The English Teacher, 2015)
The study investigates the significance of the application of Rosenblatt’s reader-response theory for teaching literature in EFL teacher education in Indonesia. As the body of literature suggests, reader response strategies potentially offer students multilayered benefits such as promoting aesthetic experience, empowering students’ voices, and improving students’ motivation and interest in reading as well as literacy (reading-writing) achievement. Reader response strategies can potentially involve readers’ cognitive and affective aspects that are indicated by their reflections of their active classroom involvement. In addition, their written reader responses may include varied strategies. The study, thus, is concerned with Beach and Marshall’s (1991) seven types of strategies: engaging, describing, conceiving, explaining, connecting, interpreting, and judging. As an effort in improving the subjects from the psychological and linguistic perspectives, the study was concerned with classroom action research. The one semester long two cycle study was focused on the Prose class. The purposively selected student teachers (N=36) of varied racial and cultural backgrounds from the third grade of the English department and the teacher as the researcher participated in the study. The progress made by the students in each cycle of the teaching as reflected in literacy events such as group and classroom discussions and writing journals were qualitatively analyzed with reference to the emerging themes of students’ response strategies. Categorization of response strategies of the subjects was based on the coded emerging reader responses with reference to aforementioned Beach and Marshall’s (1991) seven response strategies. The findings suggest that there have been improvements in terms of their boldness and self-confidence in expressing ideas, involvement in classroom activities, and linguistic growth such as writing skill. In addition, the study offers pedagogical implications for the subjects’ future classroom practices.